2015
DOI: 10.1007/s11121-015-0605-4
|View full text |Cite
|
Sign up to set email alerts
|

Changing Friend Selection in Middle School: A Social Network Analysis of a Randomized Intervention Study Designed to Prevent Adolescent Problem Behavior

Abstract: Adolescent friendships that promote problem behavior are often chosen in middle school. The current study examines the unintended impact of a randomized school based intervention on the selection of friends in middle school, as well as on observations of deviant talk with friends five years later. Participants included 998 middle school students (526 boys and 472 girls) recruited at the onset of middle school (age 11-12 years) from three public middle schools participating in the Family Check-up model interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…This finding may be of importance for recent research that suggests that people’s friendship choices can be altered (see DeLay et al 2016). If peer selection can be fluidly changed so that people befriend more “normative” peers instead of friends who are criminally-inclined, this would truthfully represent a huge step forward in research on social groups and deviance.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding may be of importance for recent research that suggests that people’s friendship choices can be altered (see DeLay et al 2016). If peer selection can be fluidly changed so that people befriend more “normative” peers instead of friends who are criminally-inclined, this would truthfully represent a huge step forward in research on social groups and deviance.…”
Section: Discussionmentioning
confidence: 75%
“…Since then, theories (e.g., Burgess and Akers 1966) and research (e.g., DeLay et al 2016) have further developed and have produced a rich knowledge on how, when, and why peers are influential for crime. In the midst of these various contributions, however, Sutherland’s (1947) differential association theory stands out.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to include five network effects recommended from prior network studies (Ripley et al, 2018): Outdegree, reciprocity, GWESP-FF, transitive triplets, and the interaction between reciprocity and transitive triplets (Block, 2015). Network effects were included (a) because their exclusion, when estimating friendship changes, leads to biases in effect estimates (Snijders et al, 2007; these network interdependencies are explained in detail in the Result section "Selection and Extraversion") and (b) because a series of prior studies on friendship networks showed that, when modeling friendship network changes, these effects significantly explain friendship network changes and, therefore, represent important confounding effects (e.g., Block & Grund, 2014;DeLay, Ha, Van Ryzin, Winter, & Dishion, 2016;Van de Bunt et al, 1999;Van Zalk et al, 2010;Van Zalk et al, 2014;Veenstra et al, 2013). We refer to the Result section for specific interpretations of each effect and the model fit section for how we assessed their model fit to the data.…”
Section: Analysis Strategymentioning
confidence: 99%
“…However, these designs do not allow researchers to examine the proportion of the adolescent's naturalistic peer group with which they discuss these topics. 1 Similarly, studies that examine selection of antisocial friends generally ask adolescents to report on the delinquent behavior of a few "best friends" (DeLay et al, 2015;Osgood et al, 2013). These restrictions on whom the adolescent is rating may further limit researchers' abilities to assess the delinquency of the broader peer network.…”
Section: Socialization Vs Selection Effects For Antisocial Behaviorsmentioning
confidence: 99%
“…Studies in which peer communication is directly observed have greatly advanced knowledge about adolescents’ antisocial communication and how it relates to deviant behavior (Dishion & Andrews, 1995; Dishion et al, 1996; Gottfredson, 2010). These studies, however, have often been limited to observing dyads (DeLay et al, 2015; Dishion et al, 1996; Piehler & Dishion, 2007; Piehler & Dishion, 2014) or observing adolescents in artificially assigned groups (Dishion & Andrews, 1995; Gottfredson, 2010; Rorie et al, 2011). Such designs allow researchers to measure the amount of communication about antisocial topics (in a particular dyad or group).…”
Section: Socialization Vs Selection Effects For Antisocial Behaviorsmentioning
confidence: 99%